Proximate composition and antioxidant potential of leaves from three varieties of mulberry (Morus sp.): a comparative study - Iqbal, Shahid; Younas, Umer; Sirajuddin; Chan, Kim Wei; Sarfraz, Raja Adil; Uddin, Md. Kamal (MDPI, 2012)
In this study, leaves of three indigenous varieties of Mulberry namely, Morus alba L., Morus nigra L. and Morus rubra L. were investigated for their antioxidant potential and their proximate composition was determined. The yields of 80% methanolic extracts ranged between 8.28–13.89%. The contents of total phenolics (TPC), total flavonoids (TFC) and ascorbic acid (AA) ranged between 16.21–24.37 mg gallic acid equivalent (GAE)/g, 26.41–31.28 mg rutin equivalent (RE)/g and 0.97–1.49 mg/g, respectively. The antioxidant activity of leaf extracts was evaluated by measuring 1,1-diphenyl-2-picrylhydrazyl (DPPH•) radical scavenging actity, 2,2'-azino-bis-(3-ethylbenzthiazoline-6-sulphonic acid (ABTS•+) radical cation scavenging capacity and ferric ion reducing power and values ranged between 1.89–2.12, 6.12–9.89 and 0.56–0.97 mM Trolox equivalent/g of dried leaves, respectively. The investigated features reveal good nutritive and antioxidant attributes of all the varieties with mutually significant differences.